Advances in Enhanced Menaquinone-7 Production From Bacillus subtilis - Liao, Chaoyong; Ayansola, Hammed; Ma, Yanbo; Ito, Koichi; Guo, Yuming; Zhang, Bingkun (Frontiers in Bioengineering and Biotechnology, 2021)
The production of nutraceutical compounds through biosynthetic approaches has received considerable attention in recent years. For example, Menaquinone-7 (MK-7), a sub-type of Vitamin K2, biosynthesized from Bacillus subtilis (B. subtilis), proved to be more efficiently produced than the conventional chemical synthesis techniques. This is possible due to the development of B. subtilis as a chassis cell during the biosynthesis stages. Hence, it is imperative to provide insights on the B. subtilis membrane permeability modifications, biofilm reactors, and fermentation optimization as advanced techniques relevant to MK-7 production. Although the traditional gene-editing method of homologous recombination improves the biosynthetic pathway, CRISPR-Cas9 could potentially resolve the drawbacks of traditional genome editing techniques. For these reasons, future studies should explore the applications of CRISPRi (CRISPR interference) and CRISPRa (CRISPR activation) system gene-editing tools in the MK-7 anabolism pathway.